2017
DOI: 10.14295/bds.2017.v20i2.1400
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Hydroxide improves epoxy sealer adhesion on root dentin

Abstract: <p><strong>Objective</strong>: The aim of this study is to evaluate the adhesion of an endodontic sealer (AHPlus in root canals after the use of different protocols of 17% EDTA and the use of intracanal medication (ICM) based on calcium hydroxide in aqueous vehicle. <strong>Material and Methods</strong>: For this, 72 single-rooted human teeth were instrumented up to #50 and divided into six groups (n = 12). Group 1: EDTA for 3 min; Group 2: 3 mL of EDTA + 3 min of EDTA; Group 3: 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, the heterogeneity between the studies was high ( I 2 = 90%; p < 0.00001). When the heterogeneous studies (outlying studies with results that conflict with the rest of the studies) were removed from the model, 24–26,28 the heterogeneity decreased to I 2 = 41% with p = 0.12; and hence, the fixed‐effect model was used (Figure 3). The difference of the residual studies was also non‐significant (SMD = −0.16; 95% CI = −0.39, 0.06; p = 0.14).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the heterogeneity between the studies was high ( I 2 = 90%; p < 0.00001). When the heterogeneous studies (outlying studies with results that conflict with the rest of the studies) were removed from the model, 24–26,28 the heterogeneity decreased to I 2 = 41% with p = 0.12; and hence, the fixed‐effect model was used (Figure 3). The difference of the residual studies was also non‐significant (SMD = −0.16; 95% CI = −0.39, 0.06; p = 0.14).…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the effect of intracanal medicaments including CH on push‐out bond strength of sealers have reported contradictory results 2,5,6,14,16–38 . While some studies claimed a negative influence of CH intracanal medicament on the bond strength of the sealers, 28,29,33,39 many others reported no any significant effect, 2,14,16,17,21,24,27,30,34,35,37,40 and some even reported positive effect 22,25,31,32,38 . Based on the available data, it seems that the effect of CH medicament on the on push‐out bond strength of sealers is still debatable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be related to the inability to remove nano-silver gel with a resinous sticky form from the root dentin walls, especially at the apical third which may be interpreted by the findings of Balvedi et al, 2010 [64] , where the circulation volume of the solution of irrigation was lower than at the coronal and middle thirds. However, Camargo et al, 2016 [65] found that no statistically significant difference was evident in the efficiency of the removal of medicaments in the three portions of the root canal (apical, middle, and coronal third). This discrepancy between the studies might have caused by various methodological variations including duration of irrigation and the amount of irrigants used, various approaches of intracanal removal, period of storage, various thickness of the section of root, and size of plunger used during the push out bond test procedures.…”
Section: Discussionmentioning
confidence: 99%